Negotiating Spain and Catalonia : competing narratives of national identity - Solís, Fernando León (Intellect, 2003)
This book is a narrative study of four main discourses of national identity in Spain, with a special focus on Catalonia as disseminated in the Spanish press in the period between 1993-1996. The narrative analysis of the discourses of national identity is contained within two sections. The first deals with Spanish press coverage of the 1994 USA Football World Cup. The second section studies the process of negotiation towards a political pact between Partido Popular and Convergència I Unió after the 1996 general election. This study is not confined to the identification and description of discursive elements intended to shape identities, but deals heavily with the symbolic struggle between different ideological agents. The narrative approach and systematic application to two particular and very concrete cases makes this work unique in its field. This book would be useful as a reference text for courses not only on Contemporary Spain, but also on the wider field of Cultural Studies and Media Studies. However, the issues dealt with and the style in which it is written, make it of interest to a wider and not necessarily academic audience.